SAE Technical Paper Series 2020
DOI: 10.4271/2020-01-0453
|View full text |Cite
|
Sign up to set email alerts
|

Electric Vehicle Cold Start Range Estimation through Battery-in-Loop Simulations within a Virtual Driving Environment

Abstract: Lithium-ion (Li-ion) batteries have become a research focus in the field of electric and hybrid electric vehicles, due to key advantages such as high specific energy, high energy density and low selfdischarge rate in comparison with other battery technologies. Nevertheless, key issues involving safety, performance, cost, charging time and durability restrict mass market adoption of electric vehicles. Cold-temperature operation of Li-ion batteries is currently a subject of major research efforts. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…67 Zhanning et al 68 demonstrates a slightly different use for the study of fuel-cell-electric hybrid vehicles. Sarmiento-Carnevali et al 69 shows the benefit of thermal conditioning with in-the-loop testing.…”
Section: Applicationsmentioning
confidence: 99%
“…67 Zhanning et al 68 demonstrates a slightly different use for the study of fuel-cell-electric hybrid vehicles. Sarmiento-Carnevali et al 69 shows the benefit of thermal conditioning with in-the-loop testing.…”
Section: Applicationsmentioning
confidence: 99%
“…Of the competing electrochemical energy storage technologies, the lithium-ion (li-ion) battery is regarded as the current leader in terms of volumetric (Whl -1 ) and gravimetric (Whkg -1 ) energy density at standard temperature conditions (20 °C) [2]. It is well documented in the literature that accessible battery capacity decreases significantly at low temperatures [3]- [7] [8]. Smart, et al [3] documented a 33% reduction in capacity (Ah) and 43% reduction in energy (Wh) when the temperature of a LiNixCo1-xO2/carbon cell was reduced from 20 °C to -30 °C with a 1.0C discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Jaguemont et al [4] recorded a 39% reduction in energy of a 100 Ah LiFeMnPO4 commercial cell under 0.5C discharge at -20 °C compared to 25 °C. Recently, Sarmiento-Carnevali et al [8] demonstrated a 30.9% reduction in electric vehicle range when reducing from 20 °C to -10 °C.…”
Section: Introductionmentioning
confidence: 99%